Exoskeletal predator defenses of juvenile California spiny lobsters (Panulirus interruptus) are affected by fluctuating ocean acidification-like conditions - Lowder, Kaitlyn B.; deVries, Maya S.; Hattingh, Ruan; Day, James M. D.; Andersson, Andreas J.; Zerofski, Phillip J.; Taylor, Jennifer R. A. (Frontiers in Marine Science, 2022)
Spiny lobsters rely on multiple biomineralized exoskeletal predator defenses that may be sensitive to ocean acidification (OA). Compromised mechanical integrity of these defensive structures may tilt predator-prey outcomes, leading to increased mortality in the lobsters’ environment. Here, we tested the effects of OA-like conditions on the mechanical integrity of selected exoskeletal defenses of juvenile California spiny lobster, Panulirus interruptus. Young spiny lobsters reside in kelp forests with dynamic carbonate chemistry due to local metabolism and photosynthesis as well as seasonal upwelling, yielding daily and seasonal fluctuations in pH. Lobsters were exposed to a series of stable and diurnally fluctuating reduced pH conditions for three months (ambient pH/stable, 7.97; reduced pH/stable 7.67; reduced pH with low fluctuations, 7.67 ± 0.05; reduced pH with high fluctuations, 7.67 ± 0.10), after which we examined the intermolt composition (Ca and Mg content), ultrastructure (cuticle and layer thickness), and mechanical properties (hardness and stiffness) of selected exoskeletal predator defenses. Cuticle ultrastructure was consistently robust to pH conditions, while mineralization and mechanical properties were variable. Notably, the carapace was less mineralized under both reduced pH treatments with fluctuations, but with no effect on material properties, and the rostral horn had lower hardness in reduced/high fluctuating conditions without a corresponding difference in mineralization. Antennal flexural stiffness was lower in reduced, stable pH conditions compared to the reduced pH treatment with high fluctuations and not correlated with changes in cuticle structure or mineralization. These results demonstrate a complex relationship between mineralization and mechanical properties of the exoskeleton under changing ocean chemistry, and that fluctuating reduced pH conditions can induce responses not observed under the stable reduced pH conditions often used in OA research. Furthermore, this study shows that some juvenile California spiny lobster exoskeletal defenses are responsive to changes in ocean carbonate chemistry, even during the intermolt period, in ways that can potentially increase susceptibility to predation among this critical life stage.